PENGARUH KOMPENSASI, LINGKUNGAN KERJA, DAN STRES KERJA TERHADAP PRODUKTIVITAS KERJA MELALUI VARIABEL INTERVENING KEPUASAN KERJA PEGAWAI: (STUDI PADA KPP PRATAMA YOGYAKARTA) - Arif Muhammad Nurhasan; Muhammad Awal Satrio Nugroho (Jurnal Riset Manajemen Akuntansi Indonesia, 2023)
The purpose of this study was to determine the effect of compensation variables, work environment variables, work stress variables on employee job satisfaction variables, determine the effect of compensation variables, work environment, and work stress on employee work productivity, determine the direct effect of job satisfaction variables on work productivity, determine the effect of compensation, work environment and work stress on work productivity through intervening variables of job satisfaction on employees at KPP Pratama Yogyakarta. The method in this research is a quantitative descriptive method. The population in this study were 100 KPP Pratama Yogyakarta employees. The technique of determining the sample using the saturated sample method is to make the entire population part of the sample. The data collection method used is using a questionnaire and for data analysis using a structural equation model. The results showed that compensation, work environment and work stress have an influence on job satisfaction. Compensation has a positive effect on job satisfaction. The work environment has a positive effect on job satisfaction. Job stress has no effect on job satisfaction. Compensation has a positive effect on work productivity. The work environment has a positive effect on work productivity. Work stress has a negative effect on work productivity. Job satisfaction has a positive effect on work productivity.